Effect of Leunca Fruit (Solanum nigrum L.) on Oxidative Stress in rats fed a High Fat High Sucrose Diet - Nurdin, Nurhanifah Muthmainnah; Muis, Siti Fatimah; Anjani, Gemala; Noer, Etika Ratna; Ayustaningwarno, Fitriyono (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Decreased levels of superoxide dismutase (SOD) and increased levels of malondialdehyde (MDA) are markers of oxidative stress and indicate obesity. Leunca fruit (Solanum Nigrum L) is a plant that contains antioxidants that can reduce the level of oxidative stress in obesity. The purpose of this study was to determine the effect of leunca fruit administration on SOD and MDA levels in obese rats. This type of research is true experimental with a post-test-only research design where 30 male Sprague Dawley rats were divided into five groups consisting of 2 control groups K(-) and K(+) and three treatment groups (P1, P2, P3). Groups K+, P1, P2, and P3 were fed a high-fat and sucrose diet (21% lard, 34% sucrose). The K (-) control group is a group of healthy rats that only receive standard feed without being given leunca fruit. Group K (+) is a group of obese rats without leunca fruit. Leunca fruit was given for six weeks at a dose of 0.8g (P1), 1.6g (P2), and 2.4g (P3). Serum SOD levels were measured by ELISA method and MDA levels were measured by TBARS method. Statistical analysis using One Way Anova test. Administration of leunca fruit with graded doses can significantly increase SOD activity p=0.000 (p<0.05) and can significantly reduce MDA levels in obese rats in each treatment group p=0.000 (p<0.05). Leunca fruit with a dose of 2.4g/BB rat is the most effective dose to increase SOD levels and reduce MDA levels. The limitation of this study that there is no weighing of the remaining rat feed at each meal, so that the percentage of rat intake is was unknown.